The UX book : Agile UX design for a quality user experience - Hartson, Rex; Pyla, Pardha S. (Morgan Kaufmann, an imprint of Elsevier, 2019)
The discipline of user experience (UX) design is maturing into a confidence practice and this edition reflects, and accelerates, that evolution. One of the major positive trends in UX is an emphasis on design -- a kind of design that highlights the designer's creative skills and insights and embodies a synthesis of technology with usability, usefulness, aesthetics, and meaningfulness to the user. In this edition a new conceptual top-down design framework is introduced to bring this trend to our readers. -- From publisher's description.
Keywords: User interfaces (Computer systems) -- Design.; Human-computer interaction.; elektronické knihy; electronic books